Interdiffusion study of the topologically closed packed μ phase and the phase boundary compositions in the Fe–Mo system. (October 2019) - Baheti, Varun A.; Raju, Ravi
Abstract: Fe/Mo bulk diffusion couples are annealed at 1050–1200 °C to study the growth and diffusion behaviour of μ phase in the Fe–Mo system. Parabolic growth constants and integrated interdiffusion coefficients are determined in the μ phase. The activation energies for the growth of μ phase and for the integrated interdiffusion coefficients are estimated as 228 ± 22 and 733 ± 10 kJ/mol, respectively. The relatively high activation energy for interdiffusion in μ phase, determined at high homologous temperature of 0.8–0.9, indicates that μ phase grows by lattice diffusion. Phase boundary compositions, measured by EPMA, indicates the homogeneity range of μ phase to be ~ 3 at.% higher towards the Fe–rich side (i.e., 36 at.% Mo) as compared to the reported composition of 39–44 at.% Mo in the phase diagram. Highlights: Interdiffusion study is conducted in the Fe–Mo system. The phase boundary compositions are measured by EPMA. Parabolic growth constants and diffusion parameters are determined in the μ phase. Our analysis indicates that diffusion process should be discussed based on diffusion parameters.